2016
DOI: 10.1177/0218492316645749
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of anatomic repair in a subgroup of corrected transposition

Abstract: Results of atrial switch-Rastelli procedures in this subgroup of patients with corrected transposition are satisfactory but still imperfect. Mitral regurgitation might predict a poor outcome. Long-term follow-up is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A total of 532 patients were finally enrolled, of which 83 met the combined end-point of n-SCD, SCD or SCD equivalent events, and HTX. All included trials were single-center types from seven countries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The average age in the described population ranged from 9.8 to 42 years, and men accounted for 36.4–67.5%, with an average follow-up time of 5.3– 20 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 532 patients were finally enrolled, of which 83 met the combined end-point of n-SCD, SCD or SCD equivalent events, and HTX. All included trials were single-center types from seven countries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The average age in the described population ranged from 9.8 to 42 years, and men accounted for 36.4–67.5%, with an average follow-up time of 5.3– 20 years.…”
Section: Resultsmentioning
confidence: 99%
“…The first group (I) includes patients after surgical correction only, while the second group (II) includes patients not operated on by any method ( Figures S1 and S2 ). After this analysis, the heterogeneity ratio decreased for subgroup I for both SVR (Inverse Variance OR 3.97 [1.41, 11.13] p = 0.009 (95% CI), I 2 = 8%) [ 9 , 10 , 14 , 18 ] and SVD (Fixed Model OR 4.69 [2.06, 10.71] p < 0.001 (95% CI), I 2 = 5%) [ 10 , 13 , 14 ]. High heterogeneity was observed in subgroup II for SVR (Inverse Variance OR 2.03 [0.01, 483.63] p = 0.8 (95% CI), I 2 = 92%), and SVD (Fixed Model OR 5.55 [1.81, 16.99] p = 0.003 (95% CI), I 2 = 82%) [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the cases reported, we found that 16 of them were older than 15 years of age by looking at the methods of each article. An electronic message reply was obtained from three of these authors, from three different institutions, who confirmed the operation was done in five patients, four of them with good follow-up [ 59 - 61 ] . In 2013, Talwar, in a case series that included patients over 15 years of age, reported 15 patients operated on.…”
Section: Managementmentioning
confidence: 99%